Impact of Accidental Eccentricity on Regular Buildings under Seismic Loads: Insights on Nepal National Building Code NBC 105:2020 - Bhattarai, Jyoti Mani; Khadka, Birendra; Dawadi, Saroj (Mid-West University Journal of Engineering & Innovation, 2025)
Accidental eccentricity is one of the most significant factors in the design of buildings against seismic activity as it affects the torsion response of the structure. This study examines the effect of accidental eccentricity on symmetric buildings by analyzing three models: 3, 5, and 7 storey rigid diaphragm models. The analysis is performed for eccentricity values of ±10%, ±5%, and 0%, and considers torsional irregularity (maximum to minimum displacement ratios), maximum drift and overturning moment. The results show that the provision of 10% of eccentricity used by the Nepal Building Code 105:2020 leads to symmetrical buildings classified as torsionally irregular with magnified displacements, drifts, and moments. This suggests potential issues with the soundness of the 10% provision, as regular buildings should not have irregularities to that degree by virtue of their design. This study highlights the necessity of continuing research and revision of the 10% eccentricity requirement to better correlate design with the realistic performance of symmetrical structures and avoid unnecessary design.